The Role of Digital 3D Scanned Models in Dental Students' Self‐Assessments in Preclinical Operative Dentistry. Issue 4 (1st April 2018) - Lee, Cliff; Kobayashi, Hiro; Lee, Samuel R.; Ohyama, Hiroe
Abstract : The aim of this study was to determine how dental student self‐assessment and faculty assessment of operative preparations compared for conventional visual assessment versus assessment of scanned digital 3D models. In 2016, all third‐year students in the Class of 2018 (N=35) at Harvard School of Dental Medicine performed preclinical exams of Class II amalgam preparations (C2AP) and Class III composite preparations (C3CP) and completed self‐assessment forms; in 2017, all third‐year students in the Class of 2019 (N=34) performed the same exams. Afterwards, the prepared typodont teeth were digitally scanned. Students self‐assessed their preparations digitally, and four faculty members graded the preparations conventionally and digitally. The results showed that, overall, the students assessed their preparations higher than the faculty assessments. The mean student‐faculty gaps for C2AP and C3CP in the conventional assessments were 11% and 5%, respectively. The mean digital student‐faculty gap for C2AP and C3CP were 8% and 2%, respectively. In the conventional assessments, preclinical performance was negatively correlated with the student‐faculty gap (r=−0.47, p<0.001). The correlations were not statistically significant with the digital assessments (p=0.39, p=0.26). Students in the bottom quartile significantly improved their self‐assessment accuracy using digital self‐assessments over conventional assessments (C2AP 10% vs. 17% and C3CP 3% vs. 10%, respectively). These results suggest that digital assessments offered a significant learning opportunity for students to critically self‐assess themselves in operative preclinical dentistry. The lower performing students benefitted the most, improving their assessment ability to the level of the rest of the class.